DEVELOPMENT OF A MULTIFACTOR AND DYNAMIC MODEL FOR MEASURING MANUFACTURING ENTERPRISES' INTANGIBLE GOODS - García Zapata, Teonila (2007)
The present investigation treats on the development of a model multifactorial and dynamicall(MFD) for the measurement of the intangible ones apllied to companies of manufacture located in Peru. The developed model will allow to prove(try) that the knowledge is the differential one of competitiveness of the companies, in spite of the fact that the traditional accounting is not enabled to measure these aspects today in day. In this work there are analyzed the companies of Peruvian manufacture to know until point his information about his indicators that they handle they serve to identify the intangible one(the intellectual capital) With the purpose of which in some moment an own(proper) model could be standardized for the measurement of the intangible ones of the companies of manufacture of Peru.